WADY WRODZONECongenital unilateral absent pulmonary artery – clinical picture, diagnosis, treatment – own experience - Żyła-Frycz, Maria; Kusa, Jacek; Kurek, Tomasz; Szkutnik, Małgorzata; Białkowski, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Background: Congenital unilateral absence of pulmonary artery (UAPA) may involve the right or left branch. Absent left pulmonary artery is more often associated with congenital heart diseases, while absent right pulmonary artery is usually present as an isolated form. Early diagnosis of UAPA, especially of the isolated form, is very important because of later consequences. Aim: Having our own material as well as published data we present symptoms, clinical data and diagnostic methods useful in making the diagnosis of UAPA as well as therapeutic procedures. Material and Methods: We analyzed a group or 6 patients (3 children and 3 adults). X-ray, ECG, and ECO were done in all cases; in some of them we performed angi o CT, MRI or haemodynamic investigation. Results: UAPA was recognized in all cases, isolated absence of RPA in one case, absence of LPA was found in 5 cases and in 4 of them it was associated with congenital heart diseases. There was diminished pulmonary marking on X-ray in all patients and ECO examination revealed the possibility of UAPA. In 2 cases the diagnosis was established during catheterization and in other cases angi o CT or MRI was done. In one patient three interventional procedures were performed. Conclusions: 1. The clinical data of UAPA are not specific. In cases with associated congenital diseases the most characteristic are symptoms caused by this malformation. 2. The early diagnosis is done on the basis of X-ray and ECO. MRI, angi o CT and haemodynamic investigation allow the final diagnosis to be established.